PENGARUH MINI HOME EDUCATION TERHADAP RASA INGIN TAHU ANAK USIA 4-5 TAHUN - Adjeng Tria Puspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is aimed at parents who have children aged 4-5 years in the village of Margatani, Kramatwatu sub-district. In this study researchers used data collection, a survey is a method used to collect information from a number of people in the form of opinions. Based on the results of data processing and data analysis, the results of research on "the effect of mini home education on the curiosity of children aged 4-5 years" can be concluded that there is a significant influence between mini home education on the curiosity of children aged 4-5 year. It can be seen from the results of the correlation coefficient showing the number 0.986 which means a very strong influence. In other implications, the mini home education method can have a positive impact on parents and children because it can strengthen the relationship between children and parents. During the learning process children will get strong benefits, interest and innovation in children. Besides that, the role of parents to children in conveying new things that children want to know.